Anthraquinone Covalent Organic Framework Hollow Tubes as Binder Microadditives in Li−S Batteries - Guo, Can; Liu, Ming; Gao, Guang‐Kuo; Tian, Xi; Zhou, Jie; Dong, Long‐Zhang; Li, Qi; Chen, Yifa; Li, Shun‐Li; Lan, Ya‐Qian (Angewandte Chemie International Edition, 2022)
The exploration of new application forms of covalent organic frameworks (COFs) in Li−S batteries that can overcome drawbacks like low conductivity or high loading when typically applied as sulfur host materials (mostly ≈20 to ≈40 wt % loading in cathode) is desirable to maximize their low‐density advantage to obtain lightweight, portable, or high‐energy‐density devices. Here, we establish that COFs could have implications as microadditives of binders (≈1 wt % in cathode), and a series of anthraquinone‐COF based hollow tubes have been prepared as model microadditives. The microadditives can strengthen the basic properties of the binder and spontaneously immobilize and catalytically convert lithium polysulfides, as proved by density functional calculations, thus showing almost doubly enhanced reversible capacity compared with that of the bare electrode. Covalent organic frameworks could have implications as microadditives of binders (≈1 wt % in cathode) and a series of anthraquinone‐COF based hollow tubes have been prepared as model microadditives to obtain a high‐performance binder in Li−S batteries.